2018
DOI: 10.1007/s00467-018-3988-1
|View full text |Cite
|
Sign up to set email alerts
|

Urinary epidermal growth factor as a prognostic marker for the progression of Alport syndrome in children

Abstract: BackgroundAlport syndrome is a rare hereditary kidney disease manifested with progressive renal failure. Considerable variation exists in terms of disease progression among patients with Alport syndrome. Identification of patients at high risk of rapid progression remains an unmet need. Urinary epidermal growth factor (uEGF) has been shown to be independently associated with risk of progression to adverse kidney outcome in multiple independent adult chronic kidney disease (CKD) cohorts. In this study, we aim t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…Urinary EGF is not a biomarker of kidney function that is specific for LN. As reported for other kidney diseases (8–18), we found that urinary EGF/Cr levels correlated inversely with the histologic equivalents of chronic renal damage, including glomerular sclerosis, interstitial fibrosis, and tubular atrophy, as well as the combination of these components, also known as the histologic chronicity index. An inverse correlation between the urinary EGF/Cr and chronic kidney damage has also been observed in several other glomerular disease cohorts (the European Renal cDNA Bank [ERCB], Clinical Phenotyping Resource and Biobank Core [C‐PROBE], Nephrotic Syndrome Study Network [NEPTUNE], and Peking University‐IgA Nephropathy [PKU‐IgAN] Consortium), some of which included patients with lupus (6).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Urinary EGF is not a biomarker of kidney function that is specific for LN. As reported for other kidney diseases (8–18), we found that urinary EGF/Cr levels correlated inversely with the histologic equivalents of chronic renal damage, including glomerular sclerosis, interstitial fibrosis, and tubular atrophy, as well as the combination of these components, also known as the histologic chronicity index. An inverse correlation between the urinary EGF/Cr and chronic kidney damage has also been observed in several other glomerular disease cohorts (the European Renal cDNA Bank [ERCB], Clinical Phenotyping Resource and Biobank Core [C‐PROBE], Nephrotic Syndrome Study Network [NEPTUNE], and Peking University‐IgA Nephropathy [PKU‐IgAN] Consortium), some of which included patients with lupus (6).…”
Section: Discussionsupporting
confidence: 80%
“…When combined with other biomarkers of kidney function at the time of flare, such as proteinuria, the eGFR, and the histologic chronicity index, the addition of urinary EGF/Cr levels improved the prognostic value of these variables. The association of baseline urinary EGF/Cr levels with adverse kidney outcomes has also been demonstrated in other glomerular disease cohorts (6), patients with Alport syndrome (14), and patients with diabetic kidney disease (11–13).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This adjustment, however, did not abolish the association of uEGF with patient age. A recent study reported that uEGF excretion decreases with age in healthy children, 24 which suggests that higher uEGF levels in younger children may represent a physiological phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Betz et al subsequently showed that a lower uEGF/Cr was associated with rapid decline in renal function in a cohort of patients with diabetes with normoalbuminuria and preserved eGFR (19). In a cohort of 117 children with confirmed Alport syndrome, Li et al demonstrated that children with Alport syndrome showed significantly lower uEGF/Cr when compared to 146 age-matched healthy children (20). Again in this population, uEGF/Cr correlated tightly with eGFR ( r = 0.75, p < 0.001), eGFR slope, and “progressors”—those who advanced to a higher CKD stage within the study follow up—were more likely to have low uEGF/Cr.…”
Section: Bulk Transcriptomic Profilingmentioning
confidence: 99%